Answer:
0.25
Explanation:
Simplifying
3h + 1 = 7h
Reorder the terms:
1 + 3h = 7h
Solving
1 + 3h = 7h
Solving for variable 'h'.
Move all terms containing h to the left, all other terms to the right.
Add '-7h' to each side of the equation.
1 + 3h + -7h = 7h + -7h
Combine like terms: 3h + -7h = -4h
1 + -4h = 7h + -7h
Combine like terms: 7h + -7h = 0
1 + -4h = 0
Add '-1' to each side of the equation.
1 + -1 + -4h = 0 + -1
Combine like terms: 1 + -1 = 0
0 + -4h = 0 + -1
-4h = 0 + -1
Combine like terms: 0 + -1 = -1
-4h = -1
Divide each side by '-4'.
h = 0.25
Simplifying
h = 0.25